RISE: Sustainability: a balancing act between conservation and development / Professor Ts. Dr Mohd Nazip Suratman - Suratman, Mohd Nazip (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
In our interview with Professor Ts Dr Mohd Nazip Suratman, we gained greater perspectives on sustainability, facing challenges in conducting research and rising above them, and insights to a prosperous future in the field of forest management. "Sustainability refers to the ability for us to maintain and sustain natural resources so that the future generation can also enjoy the resources. In my area of specialisation, the goal is sustainable forest management. This refers to the ability for the present generation to enjoy a certain amount of harvests, while at the same time being able to avoid the destruction of natural resources, so that the produce and harvests can be maintained to be enjoyed by the future generation. The important question is: what can we do to enable the future generation to enjoy the produce or the harvest at our current rate of use of resources? We are borrowing our earth from our grandchildren."